Initial public offering : voluntary disclosure and its effect on United States IPOs. - Koh, Wee Meng. (2011)
We examine the Initial Public Offerings (IPOs) in the United States (U.S.) for the relationship between the voluntary disclosure of the use of proceeds (i.e. dollar details specificity and primary reason for listing) and the i) first day underpricing ii) post-IPO accounting performance and iii) post-IPO long run stock performance. Our results suggest that IPOs with higher dollar details specificity exhibit lower first day underpricing. The same results apply to firms that state Investment or Recapitalization as their primary reasons for listing. There is no conclusive evidence to show any significant relationship between the voluntary disclosure of the use of proceeds and accounting performance except that firms that specify higher R&D expenditure in dollar details have better Return on Assets (ROA). We also find that firms that disclose higher dollar details in debt repayment will result in better post-IPO long run stock performance. On the contrary, firms that state Investment as the primary reason experience worse long run stock performance.